Integrated substance use rehabilitation in a secure forensic facility. Issue 1 (31st January 2019) - Eagle, Kerri; Ma, Trevor; Sinclair, Barbara
Abstract : Purpose: The purpose of this paper is to inform the development of an evidence-based and effective rehabilitation programme to address substance use disorders in a population of patients with severe mental illness and mental disorders detained in a secure forensic psychiatric facility. A clinical review identified a high prevalence of substance use disorders in the patient population at a secure forensic facility in Sydney, Australia with only a limited number of patients being assessed and offered interventions for substance use problems. Design/methodology/approach: A literature review was undertaken specifically looking at articles between 2009 and 2017 that considered models of care or approaches to substance use rehabilitation in patients with co-morbid psychiatric disorders. Articles were considered based on their relevance to the purpose and the environment of a secure forensic facility. Findings: The literature review emphasised the need for a cohesive model of care integrating substance use rehabilitation with mental health care. Comprehensive assessment and individualised approaches that incorporated patient choice and stages of change were considered essential components to any dual diagnosis rehabilitation programme. Practical implications: The literature regarding rehabilitation approaches for those with severe mental illness and co-morbid substance use disorders was reasonably consistent with the models of care used in relation to criminal offenders and mental illness generally. Integrated and individualised rehabilitation approaches for dual diagnosis patients could play a significant role in forensic settings. Originality/value: Limited robust evidence for substance use rehabilitation has been published. The authors consider the existing evidence base and the underlying theory behind substance use rehabilitation to propose a model for rehabilitation in secure forensic settings. This is the first known review of substance use rehabilitation involving mentally ill offenders with dual diagnoses in secure forensic settings. This paper is the original work of the authors.